Enhancing Students’ Enthusiasm for Learning Mathematics at SMP Negeri 1 Berastagi - Ferdinand Sinuhaji; Juli Loisiana Butar-Butar; Agus Susanto Ginting; Jefrin Anugrah Humendru; Daniel Ebenejer Tarigan; Hosea Tarigan; Beril Syahputera Ginting (Jurnal Pengabdian Masyarakat Bestari, 2023)
This community service aims to increase students' enthusiasm in learning sets so that students are interested in learning sets. The method used in this service is the game method in answering questions from the set. The results obtained from service activities using the game method are that students are faster at solving set problems compared to solving problems in a theoretical way. The conclusion that can be drawn from this service activity is that learning math using the game method can teach students to concentrate more in the process of learning math at school.